KETIDAKSANTUNAN BERBAHASA PADA ISLAMOPHOBIA DI MEDIA SOSIAL - Mu’aliyah Hi Asnawi (Universitas Hasanuddin, 2020)
The writer of this article intended to analyze the image of the disrespectful utterance of Islamophobia in social media. The method of qualitative research and an inductive approach was used for the whole research process. The textual data of term of Islamophobia by the social media users and the discourse analysis method were used in this article. The decision of this article was the phenomenon of the disrespectful utterance of Islamophobia in social media could be identified into two aspects according to its’ source. The first aspect was the term of Islamophobia were constructed by the external side, by the non-muslims, by the Westerns, which Islam pictured stereotypically by this group. The second aspect was the term of Islamophobia manifested from the internally Muslims, which various expressions from the radical Islam group in social media supported the beginning of Islamophobia perception.